Methods of Reforming Adverse Possession of Registered Land: A Critique: Array - Odekunle, Idris (Acta Universitatis Danubius. Juridica, 2022)
In spite of the various justifications advanced to support the law on adverse possession, the doctrine has been variously interrogated especially its capability of defeating the notion of indefeasibility of title which is a fundamental characteristic of land registration. The problems have sparked up waves of reform of the doctrine across jurisdictions and works by various scholars. The aim of any such reform is tailored towards conferring additional protection on the registered land owners against undeserving adverse possession claims, in a manner which preserves certain valuable functions performed by the doctrine. This work, using the doctrinal methodology interrogates some existing alternative methods of reform of adverse possession but finds that none of the existing methods of reform can adequately protect the interest of registered land owners. The work in its contribution to knowledge proposes restitution as a workable solution to deal with the negative effects of adverse possession of registered land, and concludes that the best way to protect the interest of registered land owners is through the application of restitution principle founded on unjust enrichment to the operation of adverse possession.